Extraction of Hydrophilic Metabolites from Plasmodium falciparum-Infected Erythrocytes for Metabolomic Analysis - Olszewski, Kellen L. (2013)
Metabolomics is an increasingly common analytical approach for investigating metabolic networks of pathogenic organisms. This may be of particular use in the study of parasitic infections due to the intrinsic metabolic connection between the parasite and its host. In vitro cultures of the malaria parasite Plasmodium falciparum present a valuable platform to elucidate the structure and dynamics of the parasite’s metabolic network and to determine the mechanisms of action of antimalarial drugs and drug resistance mutations. Accurately measuring metabolite levels requires a reproducible method for quantifying intracellular metabolites. Here we present a simple protocol for extracting hydrophilic metabolites from P. falciparum-infected erythrocyte cultures.